Unexpected and Synergistical Effects of All-Trans Retinoic Acid and TGF-β2 on Biological Aspects of 2D and 3D Cultured ARPE19 Cells - Megumi Higashide; Megumi Watanabe; Tatsuya Sato; Toshifumi Ogawa; Araya Umetsu; Soma Suzuki; Masato Furuhashi; Hiroshi Ohguro; Nami Nishikiori (Biomedicines, 2024)
Objectives: To study the effects of all-trans retinoic acid (ATRA) on TGF-β2-induced effects of human retinal pigment epithelium cells under normoxia and hypoxia conditions. Methods: Two-dimensionally (2D) and three-dimensionally (3D) cultured ARPE19 cells were subjected to cellular functional analyses by transepithelial electrical resistance (TEER) and an extracellular flux assay (2D), measurement of levels of reactive oxygen species (ROS), gene expression analyses of COL1, αSMA, Zo-1, HIF1α, and PGC1α (2D), and physical property analyses (3D). Results: Under a normoxia condition, treatment with 100 nM ATRA substantially decreased barrier function regardless of the presence of 5 ng/mL TGF-β2 in 2D ARPE19 monolayer cells. Under a hypoxia condition, treatment with ATRA conversely increased barrier function, but the effect was masked by a marked increase in effects induced by TGF-β2. Although ATRA alone did not affect cellular metabolism and ROS levels in 2D ARPE cells, treatment with ATRA under a hypoxia condition did not affect ROS levels but shifted cellular metabolism from mitochondrial respiration to glycolysis. The changes of cellular metabolism and ROS levels were more pronounced with treatment of both ATRA and TGF-β2 independently of oxygen conditions. Changes in mRNA expressions of some of the above genes suggested the involvement of synergistical regulation of cellular functions by TGF-β2 and hypoxia. In 3D ARPE spheroids, the size was decreased and the stiffness was increased by either treatment with TGF-β2 or ATRA, but these changes were unexpectedly modulated by both ATRA and TGF-β2 treatment regardless of oxygen conditions. Conclusions: The findings reported herein indicate that TGF-β2 and hypoxia synergistically and differentially induce effects in 2D and 3D cultured ARPE19 cells and that their cellular properties are significantly altered by the presence of ATRA.